RASH DECISIONS–DERMATOLOGICAL MANIFESTATIONS PRECEDING A PROGRESSIVE NEUROLOGICAL SYNDROME. Issue 11 (9th October 2013) - Doherty, Gary; Vincent, Angela; Cox, Amanda
Abstract : We describe the case of a 72 year old woman who presented with sequential cranial nerve palsies preceded by irritation, pain and a vesicular rash in the sensory distributions of the affected nerves. She had signs and symptoms suggestive of aphagia and Ramsey–Hunt syndrome. Further vesicular eruptions roughly obeying dermatomal boundaries on the limbs and trunk were observed. She was initially thought to have disseminated VZV/HZV infection and was commenced on IV aciclovir. Investigations seeking evidence for viral particles in skin lesions and CSF, and for evidence of immunosuppression or malignancy, were all negative. Between days 35 and 40 she developed hypertension, seizures, a left facial nerve palsy and encephalopathy. This was complicated by a pneumonia requiring invasive ventilation on intensive care. She developed an itchy maculopapular rash with vesiculation of all four limbs. On day 66 she developed truncal and limb rigidity, which became extreme over two weeks, and was associated with pyramidal weakness. The rash was biopsied demonstrating a leucocytoclastic vasculitis. At the nadir of her illness she was encephalopathic, tracheostomy–and NG feeding–dependent, quadriparetic and bedbound due to severe rigidity (leading rapidly to Achilles tendon contractures). She was found to be glycine receptor (GlyR) antibody positive, without antibodies against amphiphysin or GAD65. She was initially treated with a combination of corticosteroids and intravenous immunoglobulin (IVIG), resulting in resolution of her cranial nerve palsies, and a reduction in her rigidity and rash. Imaging using CT, PET, USS and mammography was undertaken to exclude malignancy–associated antibody production. MRI imaging of the brain and spinal cord was essentially normal. CSF analysis demonstrated only the presence of intrathecal IgG synthesis. Her treatment and rehabilitation continues. This case adds to the small number of reports in the literature of a Stiff Person Syndrome (SPS) plus syndrome considered to be caused by antibodies directed against the extracellular GlyR target on the synaptic neuronal surface. 1 2 Our case demonstrates further clinical variability within this unusual disorder. The GlyR is expressed in skin, and the presence of zoster–like dermatological lesions may provide a clinical clue as to the underlying aetiology in similar cases. Many of the features seen in this case have been previously described, however in this case the features emerged sequentially with rigidity, the cardinal feature of this group of diseases, emerging last. The clinical manifestations of the cases of GlyR antibody associated SPS plus disease described, closely resemble the clinical manifestations of genetic mutations of GlyR subunits and associated proteins, and of poisoning with the GlyR antagonist strychnine. This adds to the evidence that these antibodies play a direct role in the pathogenesis of disease, and that the use of immunosuppressive treatment is justified. Indeed our patient has made a substantial recovery with aggressive immunotherapy. To date no associated malignancy has been associated with GlyR antibody–mediated SPS plus disease, and our case supports these findings.